Multi-omics investigation reveals unique markers in Klebsiella pneumoniae compared to closely related species - Swiatek, Lena-Sophie; Surmann, Kristin; Eger, Elias; Müller, Justus U.; Gesell Salazar, Manuela; Heiden, Stefan E.; Werner, Guido; Hübner, Nils-Olaf; Bohnert, Jürgen A.; Becker, Karsten; Völker, Uwe; Schwabe, Michael; et al. (Frontiers in Microbiology, 2025)
IntroductionThe Klebsiella pneumoniae (KP) species complex (KpSC) comprises KP as the predominant species, and six other taxa including two subspecies each of Klebsiella variicola (KV) and Klebsiella quasipneumoniae (KQ), all capable of causing clinical infections and often challenging to differentiate. Among these, KP is by far the most clinically significant, with the emergence of multidrug-resistant and hypervirulent strains leading to severe infections and limited treatment options, underscoring the need to understand the genomic features of KP.MethodsThis study compared globally disseminated KP lineages with less abundant KV strains in synthetic human urine (SHU) across multiple omics levels to identify characteristics differentiating these closely related species. Moreover, a large genomic dataset of over 6,000 publicly available genomes of KP, KV, and KQ was constructed for comparisons to other members of the KpSC.ResultsAmong eight clinical KP strains representing four different sequence types (STs), we identified 107 genes comprising the KP-specific core genome, while these genes were absent from two selected KV genomes. Transcriptome and proteome analyses in SHU revealed different regulatory patterns between KP and KV strains, with metabolic responses playing a pivotal role. A total of 193 genes specific to the investigated KP STs were identified, exhibiting differential expression at the transcriptomic and/or proteomic levels. Comparison to the genomic dataset highlighted genes adaptively regulated or uniquely present in KP genomes. For example, certain genes for citrate metabolism are uniquely upregulated in KP and a gene cluster for the cellobiose phosphotransferase system, previously linked to bacterial virulence and biofilm formation, was found exclusively in KP.DiscussionOur study underscores the metabolic flexibility of KP strains in response to specific environmental conditions, potentially contributing to opportunistic pathogenicity. We identified markers enriched in KP STs, providing a foundation for future investigations including their relevance for diagnostics.